2018
DOI: 10.1136/bmjopen-2017-019627
|View full text |Cite
|
Sign up to set email alerts
|

What fluids are given during air ambulance treatment of patients with trauma in the UK, and what might this mean for the future? Results from the RESCUER observational cohort study

Abstract: ObjectivesWe investigated how often intravenous fluids have been delivered during physician-led prehospital treatment of patients with hypotensive trauma in the UK and which fluids were given. These data were used to estimate the potential national requirement for prehospital blood products (PHBP) if evidence from ongoing trials were to report clinical superiority.SettingThe Regional Exploration of Standard Care during Evacuation Resuscitation (RESCUER) retrospective observational study was a collaboration bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…In the RESCUER study, we demonstrated that the time interval between the emergency call and arrival of the medical team was 25 (IQR 19–35 min). The median combined on‐scene and transfer time was 53 min (IQR 39–73)…”
Section: United Kingdomsupporting
confidence: 93%
See 3 more Smart Citations
“…In the RESCUER study, we demonstrated that the time interval between the emergency call and arrival of the medical team was 25 (IQR 19–35 min). The median combined on‐scene and transfer time was 53 min (IQR 39–73)…”
Section: United Kingdomsupporting
confidence: 93%
“…The Regional Exploration of Standard Care during Evacuation Resuscitation (RESCUER) study explored the use of fluids used following hypotensive trauma in physician‐led prehospital care. We showed that, at that time, ten services carried blood and four of these had already published data …”
Section: United Kingdommentioning
confidence: 99%
See 2 more Smart Citations
“…Three out of seven services had immediate access to PHTRBC; the other four needed 45 minutes in order to obtain it. Karl et al report that 25.3% of 235 US Helicopter Emergency Medical Service (HEMS) programmes that responded to a survey carried blood, while a 2016 survey found that 10 out of the 22 HEMS in the United Kingdom carried blood products …”
Section: Resultsmentioning
confidence: 99%